The influence of communication, empowerment and trust on organizational ethical climates - Tan, Houng Chien; Ho, Jo Ann (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
In this study, communication, empowerment and trust were examined to determine their influence on an organization’s ethical climate. A total of 150 questionnaires completed by managers and executives based in the Klang Valley, Malaysia were analysed. The results demonstrated that empowerment was positively related to a benevolent-local climate while trust was positively related to both benevolent-local and principled-local climates. However, communication did not have a significant influence on all three ethical climate types. We discuss our results and the implications for both future academic research and practice.